Processo de produção de erva-mate descafeinada e de micro/nanopartículas de cafeína usando dióxido de carbono supercrítico - Brun, Gerti Weber (2012)
The decaffeination of leaves of yerba mate is economically attractive, since it allows to obtain products of commercial interest and caffeine, a byproduct used in food and pharmaceutical industries. In this work we used the extraction and precipitation with supercritical carbon dioxide to obtain the decaffeinated yerba mate and micro/nanoparticles of the caffeine. The decaffeinated yerba mate and extract were obtained from the dry leaves on automated pilot plant. The mathematical modeling was realized with the extraction curves defining the condition of the pressure and temperature for higher yield and lower caffeine content in yerba mate. For the micronization process based on the use of supercritical carbon dioxide as antisolvent (SAS process, Supercritical AntiSolvent) it was used a semi-continuous pilot plant. The influence of the initial concentration, the temperature and the pressure in the yield, in the particle size, in the morphology and polymorphism were analyzed. The results demonstrated that carbon dioxide is selective for caffeine and the condition which obtains higher yields of extract and less content of the caffeine in the extracted yerba mate was 15.0 MPa and 323,15 K . The average reduction of caffeine in yerba mate was 40%. The particles were micronized from caffeine solution with dichloromethaneand the analysis of the product showed a narrower range of sizes (2.5 to 6.5 μm) in comparison to unprocessed caffeine (12.2 μm) with an increment of the purity of caffeine. We also found that with proper selection of process parameters such as temperature, pressure and initial concentration, it is possible to produce particles of caffeine with different degrees of crystallinity and distinct quantities of polimorphics.